Disturbed Consciousness : New Essays on Psychopathology and Theories of Consciousness - Gennaro, Rocco J. (Book collections on Project MUSE., 2015)
"In Disturbed consciousness, philosophers and other scholars examine various psychopathologies in light of specific philosophical theories of consciousness. The contributing authors--some of them discussing or defending their own theoretical work--consider not only how a theory of consciousness can account for a specific psychopathological condition but also how the characteristics of a psychopathology might challenge such a theory. Thus one essay defends the higher-order thought (HOT) theory of consciousness against the charge that it cannot account for somatoparaphrenia (a delusion in which one denies ownership of a limb). Another essay argues that various attempts to explain away such anomalies within subjective theories of consciousness fail. Other essays consider such topics as the application of a model of unified consciousness to cases of brain bisection and dissociative identity disorder; prefrontal and parietal underconnectivity in autism and other psychopathologies; self-deception and the self-model theory of subjectivity; schizophrenia and the vehicle theory of consciousness; and a shift in emphasis away from an internal (or brainbound) approach to psychopathology to an interactive one. Each essay offers a distinctive perspective from the intersection of philosophy, consciousness research, and psychiatry"--MIT CogNet.